New records of stomatopod and decapod crustaceans along the Pacific coast of Mexico - Hendrickx, Michel E. (1983)
Brusca, R.C. 1980. Common intertidal invertebrates of the Gulf of California. 2d ed. Univ. Arizona Press, Tucson, 513 p. Burkenroad, M.D. 1938. The Templeton Crocker Expedition. XIII. Penaeidae from the region of Lower California and Garion Island, with descriptions of 4 new species. Zoologica, 23: 55-91. Crane, J. 1937. The Templeton Crocker Expedition. VI. Oxystomatous and dromiaceous crabs from the Gulf of California and the west coast of Lower California. Zoologica, 22: 97-108.  Efford, I.E. 1972. The distribution of the sand crab, Hippa strigillata (Stimpson) and Hippa pacifica (Dana) in the Eastern Pacific Ocean (Decapoda, Anomura). Crustaceana, 23: 119-122. Garth, J.S. 1946. Littoral brachyuran fauna of the Galapagos Archipelago. Allan Hancock Pacific Exped., 5: 341-602. Garth, J.S. 1960. Distribution and affinities of the Brachyuran Crustacea, p. 105-123. In Symposium: The biogeography of Baja California and adjacent seas, Part II. Marine Biotas. Systematic Zool., 9. Garth, J.S. 1961. Eastern Pacific Expeditions of the New York Zoological Society. XLV. Non-intertidal brachygnathous crabs from the West coast of tropical America. Part 2. Brachygnatha Brachyrhyncha. Zoologica, 46: 133-159. Glassell, S.A. 1934. Affinities of the brachyuran fauna of the Gulf of California. J. Wash. Acad. Sci., 24: 296-302. Lockington, W.N. 1877. Remarks on the Crustacea of the West coast of North America , with a catalogue of the species in the Museum of the California Academy of Sciences. Cancroidea. Calif. Acad. Sci. Proc., 7: 94-108. Luke, S.R. 1977. Catalog of the benthic invertebrate collections. I. Decapod Crustacea and Stomatopoda. 510 Ref. Ser. 77-9: 72 p. Manning, R.B. 1974. Stomatopods collected by Th. Mortensen in the Eastern Pacific region (Crustacea, Stomatopoda). Steenstrupia, Zool. Mus., Univ. Copenhagen, 3: 101-109. Pérez-Farfante, l., & B.B. Boothe, Jr. 1981. Sicyonia martini, a new rock shrimp (Decapoda, Penaeoidea) from the American Pacific. J. Crustacean Biol., 1: 424-432. Rathbun, M. J. 1937. The oxystomatous and allied crabs of America. Bull. U.S. Nat. Mus., 166: 1 -278.  Reaka, M.L., & R.B. Manning. 1980. The distributional ecology and zoogeographical relationships of stomatopod Crustacea from Pacific Costa Rica. Smithsonian Contr. Mar. Sci., 7: 1-29. van der Heiden, A.M., & M.E. Hendrickx. 1982. Inventario de la fauna marina y costera del sur de Sinaloa, México. Segundo Informe de Avance. Estación Mazatlán, Instituto de Ciencias del Mar y Limnología, UNAM. 135 p. Villalobos, A.F. 1966. Estudio de los Palaemonidae de México. I.  Macrobrachium acanthochirus n. sp., del suroeste de México. An. Inst. Biol. Univ. Mex., 37: 167-173.